THEORETICAL TRAINING FOR FUTURE PHYSICAL EDUCATION TEACHERS BASED ON DIFFERENTIATЕD APPROACH (Physical Culture and Sport: Scientific Perspective, 2022)
Effective training for future specialists in physical education and sports should be based on a comprehensive system of specialized knowledge, which is an important component of a teacher's competence. Theoretical knowledge is an essential aspect of this training.The aim of our research was to enhance the level of theoretical training in students studying sports and pedagogical disciplines by implementing differentiated learning in the educational process.To achieve this aim, we established the following objectives: developing criteria to assess the formation of the cognitive component and determining the initial level of theoretical training among students in sports and pedagogical disciplines, as well as experimentally testing the effectiveness of the proposed training program.Through conducting a survey, we obtained statistically reliable data that indicate a low level of knowledge among students who entered the faculty of physical education. For instance, our results from theoretical testing revealed that 50% of the students could not correctly answer questions related to the historical aspects of physical education, while only 6% of the students demonstrated an average level of knowledge in gymnastic terminology. These results suggest that physical education teachers may not be paying sufficient attention to developing their students' knowledge system while teaching various modules of the school curriculum.Our developed program incorporates the use of a differentiated approach when studying theoretical material. We divided study and control tasks based on levels of difficulty, enabling students to perform them according to their individual abilities and progress from simpler tasks to more complex ones.The experiment yielded significant improvement in the level of theoretical training in both groups, with the most significant changes observed in the experimental group. Based on our findings, we can conclude that the use of a differentiated approach in the educational process effectively enhances the level of theoretical training among students.
Keywords: professional training; differentiated approach; physical education; theoretical training; students